2017
DOI: 10.4103/jovr.jovr_254_15
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of macular edema in behcet disease after intravitreal bevacizumab injection

Abstract: Purpose:To investigate the effect of intravitreal bevacizumab (IVB) injection on macular edema (ME) secondary to Behcet's disease.Methods:This prospective case series included 15 patients with bilateral ME due to Behcet's disease. Intravitreal bevacizumab was injected into the more severely involved eye; the contralateral eye was evaluated as the control. Patients were followed up with comprehensive ocular examination, optical coherence tomography, and fluorescein angiography (FA) for a minimum of 6 months by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…BD is a chronic, recurrent multisystem inflammatory disorder that usually is characterized by recurrent oral aphthous ulcers, uveal infusion, genital ulcers, and cutaneous manifestations. [ 1 , 9 , 10 ] BD patients can also have symptoms including the gastrointestinal lesions, the central nervous system, vascular lesions, articular manifestations, pulmonary systems, cardiovascular systems, and renal systems. [ 11 ] However, the fundamental pathogenesis of BD is not still proven, and at present, there was no unified diagnostic criteria including serology or diagnostic tool for BD.…”
Section: Discussionmentioning
confidence: 99%
“…BD is a chronic, recurrent multisystem inflammatory disorder that usually is characterized by recurrent oral aphthous ulcers, uveal infusion, genital ulcers, and cutaneous manifestations. [ 1 , 9 , 10 ] BD patients can also have symptoms including the gastrointestinal lesions, the central nervous system, vascular lesions, articular manifestations, pulmonary systems, cardiovascular systems, and renal systems. [ 11 ] However, the fundamental pathogenesis of BD is not still proven, and at present, there was no unified diagnostic criteria including serology or diagnostic tool for BD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding tumor laterality, in this series, we found older patients with less frequent germline mutation (57% vs. 51% vs. 38% vs. 38%) or bilateral involvement (90% vs. 86% vs. 81% vs. 73%). Ghassemi et al 9 reviewed 557 cases and found that the mean age at presentation was 24.7 months in germline cases and 35.7 months in nongermline cases. Likewise, prior studies have documented the mean age at diagnosis of bilateral retinoblastoma at approximately 12 months, whereas unilateral disease is diagnosed later at a mean age of 24 months 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Macular edema is a common finding in uveitic Behc ¸et's disease and can (in addition to uveitis) also be caused by retinal vein occlusion. Chroic macular edema is responsible for 42% of persistent visual lost in patients with Behc ¸et's disease [26,27]. Optic disc hyperemia and swelling may be associated with uveitis but can also develop in the event of raised intracranial pressure.…”
Section: Key Pointsmentioning
confidence: 99%